What is spontaneous order? - Luban, D (Cambridge University Press, 2019)
Due especially to the work of Friedrich Hayek, “spontaneous order” has become an influential concept in social theory. It seeks to explain how human practices and institutions emerge as unintended consequences of myriad individual actions, and points to the limits of rationalism and conscious design in social life. The political implications of spontaneous order theory explain both the enthusiasm and the skepticism it has elicited, but its basic mechanisms remain elusive and underexamined. This article teases out the internal logic of the concept, arguing that it can be taken to mean several different things. Some are forward-looking (defining it in terms of present-day functioning), whereas others are backward-looking (defining it in terms of historical origins). Yet none of these possibilities prove fully coherent or satisfactory, suggesting that spontaneous order cannot bear the analytical weight that has been placed on it.